1992
DOI: 10.1093/brain/115.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Presence, Distribution and Spread of Productive Varicella Zoster Virus Infection in Nervous Tissues

Abstract: Nervous tissue lesions were retrospectively studied for detection of productive varicella zoster virus (VZV) infection in 33 autopsied cases, including 19 herpes zoster (HZ) (10 trigeminal, nine spinal) and 14 cases of nodular brainstem encephalitis without HZ. Immunocytochemistry for VZV antigens and in situ hybridization with a biotinylated VZV DNA probe were used on formol-fixed paraffin sections. Peripheral and central nervous system, skin and striated muscle were investigated in serial sections; available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 0 publications
5
35
0
Order By: Relevance
“…Additionally, levels of pain in the acute phase were similar in younger and older patients. These observations are consistent with clinical evidence that VZV-induced neuronal damage occurs early in HZ, as reflected in prodromal signs and symptoms (5) and significant ganglionitis and VZV antigen found in the sensory ganglion very early after HZ onset (4,6,16). These findings suggest that the zoster vaccine protects older vaccinees shortly after administration, which is consistent with observations that a protective effect was noted within the 30-day postvaccination period during the definitive trial of the current vaccine (13).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, levels of pain in the acute phase were similar in younger and older patients. These observations are consistent with clinical evidence that VZV-induced neuronal damage occurs early in HZ, as reflected in prodromal signs and symptoms (5) and significant ganglionitis and VZV antigen found in the sensory ganglion very early after HZ onset (4,6,16). These findings suggest that the zoster vaccine protects older vaccinees shortly after administration, which is consistent with observations that a protective effect was noted within the 30-day postvaccination period during the definitive trial of the current vaccine (13).…”
Section: Discussionsupporting
confidence: 87%
“…Ongoing viral replication was also suggested by Schmidbauer et al (29), who detected viral antigens (gH and nucleoprotein) and VZV DNA in ganglia from 7 patients up to 7 weeks after the onset of the herpes zoster rash. Interestingly, as in our study, they only identified viral antigens in necrotic regions of the ganglia (29). We have previously shown that VZV-infected neurons expressing IE63 are resistant to apoptosis (7).…”
Section: Discussionsupporting
confidence: 55%
“…Previous histological studies of ganglia from patients with herpes zoster close to the time of death noted necrosis in part or the whole of the ganglia, with some hemorrhage and lymphocytic infiltration (27)(28)(29)(30)(31)(32). Some cases also showed vascular involvement with perivascular lymphocytic cuffing and thrombosis noted (28,31).…”
Section: Discussionmentioning
confidence: 96%
“…Neurologic symptoms usually develop within days to weeks after the rash and present a chronic progression [1, 2], while a remitting-exacerbating course has been rarely described [3]. This clinical profile is supported by pathological studies, disclosing necrotizing inflammatory abnormalities and demyelination lesions, mainly involving the posterior horns and the dorsal columns [1, 2, 4]. The pathogenesis is not entirely understood.…”
Section: Discussionmentioning
confidence: 99%